2022
DOI: 10.1155/2022/1392896
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Ameliorated High Choline-Induced Cardiac Dysfunction by Inhibiting cGAS-STING-NLRP3 Inflammasome Pathway

Abstract: Although it is an essential nutrient, high choline intake directly or indirectly via its metabolite is associated with increased risk of cardiovascular disease, the mechanism of which remains to be elucidated. The present study was performed to investigate whether hydrogen sulfide (H2S) was involved in high choline-induced cardiac dysfunction and explore the potential mechanisms. We found that ejection fraction (EF) and fractional shortening (FS), the indicators of cardiac function measured by echocardiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…ox-LDL can induce DNA hypermethylation of the CSE promoter in macrophages, resulting in suppression of H 2 S production and CSE transcription, thereby exacerbating inflammatory responses ( 74 ). CSE deficiency or inhibition induces NLRP3 inflammasome activation in inflammatory cellular and mouse models with peritonitis, acute kidney injury, high choline-induced cardiac dysfunction, diabetic cardiomyopathy and colitis ( 40 , 70 , 75 77 ). Therefore, the present study investigated the impact of endogenous and exogenous H 2 S on macrophage pyroptosis following ox-LDL stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…ox-LDL can induce DNA hypermethylation of the CSE promoter in macrophages, resulting in suppression of H 2 S production and CSE transcription, thereby exacerbating inflammatory responses ( 74 ). CSE deficiency or inhibition induces NLRP3 inflammasome activation in inflammatory cellular and mouse models with peritonitis, acute kidney injury, high choline-induced cardiac dysfunction, diabetic cardiomyopathy and colitis ( 40 , 70 , 75 77 ). Therefore, the present study investigated the impact of endogenous and exogenous H 2 S on macrophage pyroptosis following ox-LDL stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Higher H 2 S levels also enhance pathways related to oxidative stress and cell death [65]. In the analysis of the NLRP3 inflammasome in microglial cells, some studies have shown that H 2 S treatment can inhibit the activity of the NLRP3 inflammasome [66,67]. However, some studies have also shown that H2S exposure can induce the secretion of NLRP3 inflammasome-dependent IL-1β and IL-18 in human mononuclear leukocytes [68] and broiler thymocytes [69].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, DMBut was only present in the serum and liver of CIA mice given DMB, but not in the cecum, suggesting it is not microbially derived and lending evidence to support the absorption and metabolism of DMB within the host. Another study in male C57BL/6J mice fed a high-choline diet suggested that treatment with 1.3% (v/v) DMB reduced IL-1β protein expression in heart tissue through acting on cGAS-STING upstream of NLRP3 expression in macrophages, though this effect was attributed to the presumed inhibition of TMAO production by DMB [71]. In light of our results demonstrating that DMB is present in the host both in its native form and its fatty acid and acylcarnitine conjugates, the effect of DMB and its metabolites on in ammasome activation and IL-1β processing, independent of TMA/TMAO production, must be considered.…”
Section: Discussionmentioning
confidence: 99%